Exact statistical thermodynamics of alkane binary mixtures in zeolites: New interpretation of the adsorption preference reversal phenomenon from multisite-occupancy theory - Davila, Mara Veronica (2009)
The rigorous statistical thermodynamics of mixtures of polyatomic species adsorbed on one-dimensional substrates is presented. The thermodynamic functions calculated for a monomer-dimer mixture are applied to describe the adsorption of methane-ethane mixtures in zeolites. The theoretical formalism reproduces the main features of the system, showing that the displacement of ethane by methane at higher pressures, a phenomenon known as Adsorption Preference Reversal, is the result of the difference of size (or number of occupied sites) between the adsorbed species.